Challenges and solutions for nanofiltration membranes in water treatment - Su, Minghan; Zhang, Yujing; Liu, Shunda; Wang, Yafei; Li, Tiantian (Frontiers in Chemical Engineering, 2025)
Nanofiltration (NF) membranes are a pressure-driven membrane separation technology that lies between reverse osmosis (RO) and ultrafiltration (UF), featuring selective separation of low-molecular-weight organic compounds, divalent ions, and some monovalent ions. Due to their low operating pressure, low energy consumption, and ability to efficiently desalinate while retaining some beneficial minerals, NF membranes have shown broad application prospects in drinking water purification, wastewater treatment, food and pharmaceutical industries, and resource recovery. This article systematically reviews the existing challenges (including trade-off effect between selectivity and flux, membrane fouling and insufficient chemical stability) and the corresponding countermeasures from the perspectives of material modification and structural design, etc., with the aim of providing references for further research and industrial application of NF membranes.